Additive screening and formula optimization of microbial inhibitor having disease prevention and growth promotion effects on Avena sativa - Zhang, Jiangui; Yao, Tuo; Gong, Wenlong; Gao, Yamin; Zhao, Guiqin (Frontiers in Microbiology, 2023)
In order to develop environment friendly microbial inhibitor that can also control disease and promote oat (Avena sativa) growth, the growth rate method and response surface methodology were used to screen wetting agents, preservatives and protective agents at optimal concentrations in this study. Antagonistic activity of the tested bacterium and cell-free fermentation liquid against pathogenic fungi was evaluated on potato dextrose agar (PDA) substratum plates by dual culture technique. Oxford cup method was used to measure antagonistic reaction between screened bacteria. According to each screened bacteria with 50 mL were mixed and cultured in Luria-bertani (LB) substratum. Additives of Wetting agents, UV-protectors, and preservatives were screened by single factor test on the growth concentration of screened mixed bacteria. Afterwards, the optimal additives and concentrations were screened by Box-Behnken method. The microbial inhibitor was detected according to national standards GB20287-2006 and tested on oat in a pot experiment. The results showed that: (1) Functional bacteria which including Bacillus velezensis and Brevundimonas faecalis had control effects of 50.00% to 83.29% on three pathogenic fungi, and their cell free-fermentation liquid could inhibit the growth of pathogenic fungi from 23.51% to 39.90%; (2) Tween-80 was most suitable as wetting agents for Mix biocontrol bacteria (MBB) with 1.00% mass fraction; Sorbitol was selected as UV protective agents for MBB with 0.50% mass fraction. And methyl paraben was used as a preservative for MBB, with 0.50% mass fraction; (3) The most effective adjuvant contained 14.96 mL/L Tween-80, 5.12 g/L methylparaben and 5.6 g/L sorbitol; and (4) The microbial inhibitor controlled 45.57% of oat root rot and increased plant height, root length and seedling biomass.